2021
DOI: 10.1002/ana.26133
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal CSF Iron Pathway Proteins in Posthemorrhagic Hydrocephalus: Associations with Ventricle Size and Neurodevelopmental Outcomes

Abstract: Iron has been implicated in the pathogenesis of brain injury and hydrocephalus after preterm germinal matrix hemorrhage-intraventricular hemorrhage, however, it is unknown how external or endogenous intraventricular clearance of iron pathway proteins affect the outcome in this group. Methods: This prospective multicenter cohort included patients with posthemorrhagic hydrocephalus (PHH) who underwent (1) temporary and permanent cerebrospinal fluid (CSF) diversion and (2) Bayley Scales of Infant Development-III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
3
6
0
Order By: Relevance
“…The change in sodium concentration contributes over 50% of the change in osmolality (Table 4 ). However, protein concentration is believed to contribute only minimally to osmolality [ 29 , 37 ] and similarly, our results show that change in protein concentration only contributes about 8% to osmolality change (Table 4 ). In addition, compared to control, total protein concentrations are increased in both HGIVH and PHH but osmolality, sodium, and chloride concentrations are increased in PHH only.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The change in sodium concentration contributes over 50% of the change in osmolality (Table 4 ). However, protein concentration is believed to contribute only minimally to osmolality [ 29 , 37 ] and similarly, our results show that change in protein concentration only contributes about 8% to osmolality change (Table 4 ). In addition, compared to control, total protein concentrations are increased in both HGIVH and PHH but osmolality, sodium, and chloride concentrations are increased in PHH only.…”
Section: Discussionsupporting
confidence: 84%
“…However, the increased total protein may be related to blood and its metabolites. Other studies [ 6 , 29 ] have also shown increased total protein in PHH as well as increased hemoglobin, other blood metabolites, and hemoglobin associated proteins in PHH. Further emphasizing the possible involvement of inflammation in CSF biochemical profile changes is decreased glucose in PHH compared to control, LGIVH, and HGIVH.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The contents of I C-terminal propeptide (PICP), N-terminal procollagen III, propeptide (PIIINP), hyaluronic acid (HA), and laminin (LN) in the cerebrospinal fluid of patients with chronic hydrocephalus after craniocerebral trauma were significantly higher than those in the control group ( 34 , 35 ), suggesting that the subarachnoid space and arachnoid granulations of the patients had obvious fibrosis formation, which may be the pathological basis of chronic hydrocephalus after TBI ( 34 ). In a PHH study on children, longitudinal changes in CSF transferring (increased) and ferritin (decreased) levels were associated with ventricular changes and improved neurodevelopmental outcomes ( 36 ). In addition, interleukin-10 (IL-10), interleukin-6 (IL-6), interleukin-8 (IL-8), matrix metalloprotein-7 (MMP-7), and matrix metalloprotein-9 (MMP-9) levels were significantly elevated in the CSF protein analysis of PHH ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of those neonates who develop high grade IVH, about 25-30% develop post-hemorrhagic hydrocephalus (PHH) [1,2]. Left untreated, hydrocephalus can contribute to white matter injury, seizures, cognitive impairment and even death [3].…”
Section: Introductionmentioning
confidence: 99%